Room-temperature Suzuki–Miyaura coupling of heteroaryl chlorides and tosylates - Yang, Junfeng (2013)
Suzuki–Miyaura coupling of heteroaryls is an important method for the preparation of compound libraries for medicinal chemistry and materials research. Although many catalysts have been developed, none of them have been generally applicable to the coupling reactions of heteroaryl chlorides and tosylates at room temperature. We discovered that a catalyst combination of Pd(OAc)2 and XPhos (2-dicyclohexylphosphanyl-2′,4′,6′-triisopropylbiphenyl) could efficiently catalyze these couplings. Besides the choice of catalyst, the use of hydroxide bases in an aqueous alcoholic solvent was essential for fast couplings. These conditions promoted fast release of active catalyst (XPhos)Pd0, and accelerated the transmetalation in the catalytic cycle. Most of the major families of heteroaryl chlorides (31 examples) and tosylates (17 examples) reached full conversion within minutes to hours at room temperature. The method could be easily scaled up for gram-scale synthesis. Furthermore, we examined the relative reactivity of coupling partners in whole reactions. Electron-rich heteroaryl chlorides and tosylates reacted more slowly than electron-deficient ones, in the order of indole, pyrrole < furan, thiophene < pyridine and other six-membered-ring azines. For heteroarylboronic acids, the reactivity ranking was reversed: indole, pyrrole > furan, thiophene > pyridine. Similarly, electron-deficient arylboronic acids were less reactive than electron-neutral and electron-rich ones. The reactivity trends from this study can help to choose appropriate coupling partners for Suzuki reactions.